Structural, Thermal, Morphological, Adsorption and Catalytic Properties of Poly(BPDAH-co-ODA/PPDA)-Ag/V2O5 Nanocomposites - Govindharajan Sribala; Balakrishnan Meenarathi; Ramasamy Anbarasan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Thermally stable polyimides (PIs) were prepared by condensation technique at 160 ºC for 5 hours in N-methylpyrrolidone (NMP) medium under N2 atmosphere both in the presence and absence of metal (Ag) and metaloxide (MO) (V2O5) nanoparticles (NPs). The synthesized polymers are characterized by Fourier Transform Infra Red (FT-IR) spectroscopy, 1H Nuclear Magnetic Resonance (1H NMR) spectroscopy, Differential Scanning Calorimetry (DSC), Thermal Gravimetric Analysis (TGA), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Field Emission Scanning Electron Microscopy with Energy Dispersive X-Ray (FE-SEM and EDX). The FT-IR spectrum showed a peak at 1786 cm-1 corresponding to the C=O stretching of dianhydride. The aromatic proton signals appeared between 6.7 and 7.5 ppm in the 1H-NMR spectrum of the resultant PIs. The oxydianiline (ODA) based PI with Ag NP loaded system exhibited the highest Tg value. The apparent rate constant values for the adsorption and catalytic reduction of p-nitrophenol (PNP), Cr6+ and rhodamine 6G (R6G) dye were determined with the help of UV-visible spectrophotometer. Among the catalysts, the system loaded with V2O5 NP has higher kapp values. The experimental results are critically analyzed and compared with the previously available literature values. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).